LEGAL AND CRIMINOLOGICAL ANALYSIS OF THE AGE OF ORDINARY CRIMINAL RESPONSIBILITY TO SIXTEEN YEARS IN PERU - Espinoza Bonifaz, Augusto Renzo (2026)
The author analyzes Law No. 32330, which lowers the age of criminal responsibility from 18 to 16, from a legal and criminological perspective. The research indicates that this amendment responds to a social perception of insecurity and media pressure, but contravenes constitutional principles, international human rights standards, and criminological theories on juvenile delinquency. The study employs a qualitative and interdisciplinary approach, based on normative and theoretical analysis. It concludes that the reform violates the "principle of the best interests of the child" and the constitutional framework. From a criminological standpoint, it is demonstrated that juvenile delinquency has structural causes, such as social exclusion and community disorganization, rendering a punitive response ineffective in preventing crime. Instead of reducing crime, the measure may exacerbate the situation by reinforcing the exclusion and stigmatization of adolescents. The author recommends public policies focused on prevention, education, restorative justice, and social inclusion as more effective strategies that are consistent with the constitutional framework and human rights.